Correlation between wing bone microstructure and different flight styles: The case of the griffon vulture (gyps fulvus) and greater flamingo (phoenicopterus roseus). Issue 1 (1st March 2021) - Frongia, Gian N.; Naitana, Salvatore; Farina, Vittorio; Gadau, Sergio D.; Stefano, Marco D.; Muzzeddu, Marco; Leoni, Giovanni; Zedda, Marco
Abstract: Flying is the main means of locomotion for most avian species, and it requires a series of adaptations of the skeleton and of feather distribution on the wing. Flight type is directly associated with the mechanical constraints during flight, which condition both the morphology and microscopic structure of the bones. Three primary flight styles are adopted by avian species: flapping, gliding, and soaring, with different loads among the main wing bones. The purpose of this study was to evaluate the cross‐sectional microstructure of the most important skeletal wing bones, humerus, radius, ulna, and carpometacarpus, in griffon vultures ( Gyps fulvus ) and greater flamingos ( Phoenicopterus roseus ). These two species show a flapping and soaring flight style, respectively. Densitometry, morphology, and laminarity index were assessed from the main bones of the wing of 10 griffon vultures and 10 flamingos. Regarding bone mineral content, griffon vultures generally displayed a higher mineral density than flamingos. Regarding the morphology of the crucial wing bones involved in flight, while a very slightly longer humerus was observed in the radius and ulna of flamingos, the ulna in griffons was clearly longer than other bones. The laminarity index was significantly higher in griffons. The results of the present study highlight how the mechanics of different types of flight may affect the biomechanical properties of the wing bones most engaged during flight. Abstract : "This study is based on comparative analysis about the possible effects of flying style on morphometric aspects of the wing bones of greater flamingo (Phoenicopterus roseus) (a) and griffon vulture (Gyps fulvus) (b). Our experiments underline that the griffon's wing bones display both higher laminarity index and bone mineral content than flamingo. The study may support evidence that the mechanics of different types of flight may act on both biomechanical and morphometric properties of the bones most engaged in flight."